The media, the public and agricultural biotechnology [ - Brossard, Dominique; Nesbitt, T. Clint; Shanahan, James (CABI, 2007)
Reviews the literature on communication about biotechnology. With the use of case studies, this book looks at public opinion data, communication theory, and international examples; and provides a complementary overview of how the public sees this controersial topic.